2018
DOI: 10.14744/anatoljcardiol.2017.8041
|View full text |Cite
|
Sign up to set email alerts
|

The value of real-time myocardial contrast echocardiography for detecting coronary microcirculation function in coronary artery disease patients

Abstract: Objective:The aim of this study was to evaluate the value of real-time myocardial contrast echocardiography (RT-MCE) for detecting coronary microcirculation (CM) function in coronary artery disease (CAD) patients.Methods:Sixty-five consecutive patients were divided into CAD (n=52) and no-CAD (n=13) groups using coronary angiography (CAG). All patients underwent RT-MCE at rest and CAG within 1 week after RT-MCE. The ventricular segments in CAD patients were divided semi-quantitatively into ischemic and non-isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The A × β < 2.75 ( 20 , 21 ) is the gold standard for myocardial ischemia, with the cut-off for iFR of 0.85 for the diagnosis of coronary microcirculation. The sensitivity and specificity values for iFR-based detection of myocardial ischemia were 90.7 and 89.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The A × β < 2.75 ( 20 , 21 ) is the gold standard for myocardial ischemia, with the cut-off for iFR of 0.85 for the diagnosis of coronary microcirculation. The sensitivity and specificity values for iFR-based detection of myocardial ischemia were 90.7 and 89.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…RT-MCE is a reliable method for evaluating regional myocardial perfusion. It has been reported that MBF measurements obtained by intermittent and quantitative RT-MCE techniques are well correlated with Doppler blood flow measurements in animals and humans ( 20 , 21 ). In the present study, the correlation between iFR and MCE was compared from the perspective of myocardial perfusion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of our knowledge about the regulation of coronary circulation and the characteristics of coronary perfusion are based on measurements obtained from epicardial coronary artery and tissue perfusion measurements. However, the measurements obtained from the epicardial coronary artery may mask the true blood ow of myocardial vessels due to its main function [32] . The coronary artery system is composed of three parts with different functions: the proximal segment is represented by the epicardial coronary artery, which has the volume function; the middle segment is represented by the anterior artery, which has the function of maintaining the pressure at the beginning of the small artery within a narrow range; and the distal segment is represented by the intramural small artery, which has the function of matching myocardial blood supply and oxygen consumption [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of our knowledge about the regulation of coronary circulation and the characteristics of coronary perfusion are based on measurements obtained from epicardial coronary artery and tissue perfusion measurements. However, the measurements obtained from the epicardial coronary artery may mask the true blood ow of myocardial vessels due to its main function [31] .…”
Section: Discussionmentioning
confidence: 99%